IgG4-Related Disease. Issue 15 (April 2015) - Inoue, Dai; Yoshida, Kotaro; Yoneda, Norihide; Ozaki, Kumi; Matsubara, Takashi; Nagai, Keiichi; Okumura, Kenichirou; Toshima, Fumihito; Toyama, Jun; Minami, Tetsuya; Matsui, Osamu; Gabata, Toshifumi; et al.
<x xml:space="preserve">Abstract</x> Abstract Immunoglobulin G4-related disease (IgG4-RD) is a recently discovered systemic condition, in which various organ manifestations are linked by a similar histological appearance. Our knowledge of this condition is still fragmented, as most studies have examined only a few dozen patients or focused on a particular organ manifestation. This study was conducted to learn the demography and patient characteristics of IgG4-RD using a large cohort. A total of 235 consecutive patients with IgG4-RD, diagnosed in 8 general hospitals in the same medical district, were identified by searching the institutions' radiology database. Inclusion criteria were histology-proven IgG4-RD according to the Pathology Consensus Statement and/or definitive type 1 autoimmune pancreatitis meeting the International Consensus Diagnostic Criteria. Clinical notes and images of selected patients were retrospectively reviewed. All patients were adults (M/F = 4/1). The median age was 67 years (range 35–86). Nine tenths were diagnosed in their 50s to 70s. Among 486 manifestations identified in total, the most common was pancreatitis diagnosed in 142 patients (60%), followed by sialadenitis (34%), tubulointerstitial nephritis (23%), dacryoadenitis (23%), and periaortitis (20%). The majority of patients (95%) had at least 1 of the 5 most common manifestations. Male and female patients differed in their organ manifestations (periaortitis more common in males and sialodacryoadenitis more common in females). Serum IgG4 (normal ⩽135 mg/dL) was elevated to >135 mg/dL in 208 patients (88%) and >270 mg/dL in 167 (71%). The IgG4 value was significantly higher in patients with multiorgan involvement than in those with a single manifestation (median 629 mg/dL vs 299 mg/dL, P < 0.01). Of 218 patients, for whom both IgG4 and IgG values were available, the IgG4/IgG ratio was raised to >10% in 194 (89%). Corticosteroids were effective, but the relapse rate was estimated to be 24% in the study period (median 37 months). During the follow-up, 15 malignant diseases were diagnosed in 13 patients (6%). This figure is similar to the incidence (12.9 cancers) expected from the Japanese nationwide study for cancer epidemiology (standardized incidence ratio 1.16). In conclusion, this reliable dataset could improve the characterization of IgG4-RD, particularly its unique demography and the frequency of each organ manifestation.